Importance of the crocodile (Crocodylus moreletii) in the coastal wetlands of Tamaulipas, México - Cienfuegos-Rivas, Eugenia (Universidad Autónoma de Tamaulipas, 2011)
In order to provide information about the importance of the Morelet´s crocodile to wetlands in the state of Tamaulipas, about the scientific contributions that are available for this wildlife species and the possible forms of sustainable use, a scientific compilation was performed to evaluate, appreciate and understand this natural resource, the wetland ecosystems where they live and wildlife species that cohabit with them.